One crazy summer - Williams-Garcia, Rita. (New York Scholastic Inc., 2010)
In the summer of 1968, after travelling from Brooklyn to Oakland, California, to spend a month with the mother they barely know, eleven-year-old Delphine and her two younger sisters arrive to a cold welcome as they discover that their mother, a dedicated poet and printer, is resentful of the intrusion of their visit and wants them to attend a nearby Black Panther summer camp.
Sequel: P.S. Be eleven.
Ages 9-12.
Keywords: Black Panther Party -- Fiction; Sisters -- Fiction; Mothers -- Fiction; Poets -- Fiction; African Americans -- Fiction; Civil rights movements -- Fiction; Oakland (Calif.) -- History -- 20th century -- Fiction